Computational identification of indispensable virulence proteins of Salmonella Typhi CT18 - Pawar, Shrikant; Ashraf, Md. Izhar; Mehata, Kondamudi Manobhai; Lahiri, Chandrajit * (InTech Open, 2017)
Typhoid infections have become an alarming concern with the increase of multidrug resistant strains of Salmonella serovars. The new pathogenic Gram-negative strains are resistant to most antibiotics such as chloramphenicol, ampicillin, trimethoprim, ciprofloxacin and even co-trimoxazole and their derivatives thereby causing numerous outbreaks in the Indian subcontinent, Southeast Asian and African countries. Conventional and modern methods of typing had been adopted to differentiate outbreak strains. However, identifying the most indispensable proteins from the complete set of proteins of the whole genome of Salmonella sp., comprising the Salmonella pathogenicity islands (SPI) responsible for virulence, has remained an ever challenging task. We have adopted a network-based method to figure out, albeit theoretically, the most significant proteins which might be involved in the resistance to antibiotics of the Salmonella sp. An understanding of the above will provide insight into conditions that are encountered by this pathogen during the course of infection, which will further contribute in identifying new targets for antimicrobial agents.